Assessment of Beta Angle among the various Facial Types in Garhwali Population - A Cephalometric Evaluation - Prasad, P Narayana; Ansari, Rubina; Rana, Tarun; Rawat, Nimme (Orthodontic Journal of Nepal, 2013)
Objective: The purpose of the study was to evaluate Beta (β) angle variation in different facial types among Garhwali population and also to evaluate the differences in Beta angle in male and female subgroups. Materials & Method: The sample included pre-treatment lateral cephalograms of 90 native Garhwali subjects (age 16-24 years) who were divided into three groups: normodivergent, hypodivergent and hyperdivergent; of 30 subjects of each group 15 were male and 15 were female. Result: In Garhwali population subjects with a β angle between 28° to 32° have a normodivergent facial type (ANOVA p < 0.01). Conclusion: There is a significant difference in the mean values of β angle in Garhwali population among various facial types. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9280 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 37-40